Phototransistor Based Position Sensitive Detector for Signal Detection in Photothermal Spectroscopy - Kusminarto Kusminarto; Susilo Susilo (Jurnal Matematika & Sains, 2004)
In a photothermal spectroscopy the signal change is indicated by the displacement of the probe laser beam, therefore a position sensitive detector (PSD) is required to record this displacement that is proportional to the intensity of the signal.A phototransistor (BPY62D) based PSD has been designed and constructed. A Darlington circuit has been employed to increase the sensitivity of the PSD. Sensitivity of 100.6 mV/mm has been achieved which covered a linear area of 0,5 mm.